Joint Responsibility Shared Rewards : The Managing Director's Global Policy Agenda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2019)
International cooperation, economic and financial integration, and technological progress have delivered enormous benefits across the globe during the past decades. Yet, in many countries, these benefits have not been shared adequately to prevent eroding trust in institutions and weakening support for the global system that has made these gains possible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet